2015
DOI: 10.14238/pi55.3.2015.01
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of hearing loss in children with solid tumors treated with platinum-based chemotherapy

Abstract: Background The platinum-based chemotherapy drugs, cisplatin and carboplatin, are widely used in the treatment of several types of solid tumors. However, the treatment has side effects including hearing loss. Objective To evaluate the prevalence of hearing loss related to platinum-based chemotherapy and to identify associated factors. Methods A cross-sectional study was performed in Adam Malik Hospital, Medan, North Sumatera, from April to July 2012. Twenty-two subjects who fulfilled the eligibility criteria un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(23 reference statements)
0
2
0
1
Order By: Relevance
“…A total of 994 non-duplicate citations were identified by using the selected keywords. After the final review, 66 articles were eligible for inclusion in this study [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] . The study selection process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 994 non-duplicate citations were identified by using the selected keywords. After the final review, 66 articles were eligible for inclusion in this study [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] . The study selection process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…16 DNA repair diinduksi melalui sistem nucleotide excision repair (NER), excision repair cross-complementation group 1 (ERCC1), dan xeroderma pigmentosum (XP), dimana secara bersamaan akan menggantikan kerusakan DNA selanjutnnya akan terjadi polimerase dan ligase akan terisi gap oleh DNA untai normal. 16 Menurut penelitian dari 18 Ototoksisitas yang dilaporkan terjadi pada setiap waktu, mulai dari hitungan jam hingga hari setelah kemoterapi dan ototoksisitas ini terjadi secara permanen, bilateral, dan adanya gangguan pendengaran sensorineural. 17,18 Tercatat 30 hingga 100 persen pasien kemoterapi cisplatin mengalami dampak dari efek samping khususnya gangguan pendengaran.…”
Section: Original Articleunclassified
“…Osteosarcoma is the most common primary malignant bone tumor and a leading cause of cancer death in adolescents ( 1 ). During the last decade, several strategies have been suggested for the treatment of osteosarcoma patients, but unfortunately some patients died of pulmonary metastases ( 2–5 ). Therefore, it is urgent to explore the molecular mechanisms underlying osteosarcoma carcinogenesis and progression in order to improve the prevention and treatment of this disease.…”
Section: Introductionmentioning
confidence: 99%